Laevistrombus Abbott 1960 (Gastropoda: Strombidae): Indian and southwest Pacific species - Maxwell, Stephen J.; Dekkers, Aart M.; Rymer, Tasmin L.; Congdon, Bradley C. (Zootaxa, 2019)
Here we evaluate the taxonomy of the marine gastropod genus Laevistrombus Abbott, 1960 and determine that there are five extant species within this genus, three of which occur in the southwest Pacific. Comparative analyses of this complex have been problematic due to the lack of designated type material. Therefore, we present the type material for L. canarium Linnaeus, 1758; L. taeniatus Quoy & Gaimard, 1834; and L. vanikorensis Quoy & Gaimard, 1834. Current taxonomy has L. vanikorensis absorbed within the L. canarium complex. L. taeniatus is generally held to be a synonym of L. turturella Röding, 1789. We demonstrate that both L. taeniatus and L. vanikorensis are distinct species and reinstate both to species level. Our revision also notes the significant variability in early teleoconch structure within the geographic range of L. vanikorensis, and highlights the need for a greater revision of Laevistrombus, given the diversity in early teleoconch morphology present in southwest Pacific species.